PERLINDUNGAN SIPIL DALAM MISI PASUKAN PERDAMAIAN: TANTANGAN DAN SOLUSI (STUDI KASUS UNAMID DI DARFUR) - Zhafirah Azzahra Juniusyani; Ikhwan Syahtaria; Tri Panca Titis Abriansyah; Pujo Widodo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Civilian protection in peacekeeping missions is important in both war and peace situations. Civilian protection in peace missions faces various challenges in its implementation. Civilian protection efforts involve a variety of strategies designed to reduce risks and protect civilians from the dangers of armed conflict. These challenges include limited resources and personnel, security instability, and the complexity of relationships with various related parties. These factors pose significant obstacles to the effectiveness of peacekeepers in carrying out their duties. The research method used in this paper is a quantitative approach with a literature review design. By using a library review design, researchers can investigate the problems in the research. The findings of this research indicate that civilian protection in peacekeeping missions requires a comprehensive, holistic approach. This approach must involve synergy and collaboration between various related parties to achieve optimal results. Civilian protection is not only limited to physical security from threats of violence, but also includes social, humanitarian and political dimensions that are interrelated and very complex.